2014
DOI: 10.2147/ott.s49480
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of daratumumab in the treatment of multiple myeloma

Abstract: Multiple myeloma is the second most common hematologic malignancy in the US. Treatments utilizing alkylating agents, corticosteroids, proteasome inhibitors, and immunomodulatory drugs have resulted in significant survival benefits, however, despite the advances, relapse is inevitable. Decreased depth and duration of response obtained with each successive relapse of disease is typical of the disease course, thereby highlighting a continuing need for new treatment options. With the introduction of monoclonal ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Figure 1 shows some representative aberrant immunophenotype of neoplastic plasma cells. The development and use of therapeutic anti-CD38 antibodies, such as daratumumab [ 22 ], which could reduce the expression of CD38 on the plasma cells, has also made it necessary to search for alternative markers for the identification of normal or neoplastic plasma cells. CD269, CD319, CD229, and CD54 have been found to be valuable for this purpose.…”
Section: Multi-parameter Flow Cytometrymentioning
confidence: 99%
“…Figure 1 shows some representative aberrant immunophenotype of neoplastic plasma cells. The development and use of therapeutic anti-CD38 antibodies, such as daratumumab [ 22 ], which could reduce the expression of CD38 on the plasma cells, has also made it necessary to search for alternative markers for the identification of normal or neoplastic plasma cells. CD269, CD319, CD229, and CD54 have been found to be valuable for this purpose.…”
Section: Multi-parameter Flow Cytometrymentioning
confidence: 99%
“…139 Even though the discovery of these mAb therapies offer a new avenue by which we can approach the detection of multiple myeloma, they have made the search for alternative markers to identify both normal and neoplastic PCs by MFC a priority. 140 Independent investigators have reported the expression of CD54, CD229, CD269, and CD319 to be valuable for this purpose. 54,141,142 In particular, CD269 and CD319 were found to be more versatile markers and withstood storage longer than CD138.…”
Section: Discussionmentioning
confidence: 99%
“…Daratumumab, an IgG1-k fully human anti-CD38 monoclonal antibody, exerts its cytotoxic effect through a number of mechanisms after binding to CD38, including antibody-dependent cell-mediated cytotoxicity (ADCC), complement-dependent cytotoxicity (CDC), antibody-dependent cell-mediated phagocytosis (ADCP), and the direct induction of apoptosis [ 12 , 13 ]. Moreover, an immunomodulatory effect of daratumumab was also recently described [ 14 ]. The safety of daratumumab was investigated in a dose-escalation phase I/II trial of 104 patients with relapsed or refractory multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%